Arnold O. Beckman with 200 Channel Automatic Recorder - Rothschild Photo (1960)
This recorder could take electronic signals coming from many different gauges, convert the signals into digital format, and then record all the data on a separate, connected device (a Flexiwriter). The large control panel of this recorder contains two hundred calibrating knobs, each attached to a Helipot potentiometer. This instrument was intended for use in chemical plants, but was also, in principle, the precursor to telemetric data processing systems developed by Beckman for the aerospace industry in the 1960s.
Keywords: Beckman, Arnold O.; Scientific apparatus and instruments; Beckman Instruments, Inc.